Communicative Acts as Reflections of Embodiment: The Notions of Convention and Mutual Knowledge Revisited - Žic Fuchs, Milena (Array, 2012)
Cognitive Linguistics has from its very beginnings not only recognized but built upon the notion of the ‘embodied mind’ as fundamental to understanding language (Lakoff 1987, Langacker 1987, Lakoff and Johnson 1999). Fundamental notions that form the backbone of the Cognitive Linguistic theoretical framework, notions such as concepts, categorization, metaphor, metonymy, etc. are seen as being a consequence of human biological makeup, more specifically they are shaped by our bodies and brains, especially in terms of the human sensimotor system. However, although much of Cognitive Linguistics is (at least) declaratively usage-based (Langacker 1987, 1991) there still remains a theoretical gap (as well as lack of research) between what has traditionally been subsumed under ‘pragmatics’ and ‘sociolinguistics’ and the embodied view of language. From the Gricean (1975) postulates on conversation, which can be interpreted at the same time as purposive (social) and rational (cognitive) behavior, right up to Relevance Theory (Sperber and Wilson, 1995), which in general terms represents a cognitive pragmatics perspective on communication, a strong slant towards the cognitive foundations of communication has become evident. Major works both in pragmatics as well as those in Cognitive Linguistics stress the importance of basic notions such as convention and mutual/shared knowledge, but in principle these notions are described in very general terms. It is specifically these basic concepts that we will attempt to clarify further both from the embodied/conceptual view, but also from the pragmatic perspective. A further elucidation of convention and mutual/shared knowledge will be based on an analysis of text messages in Croatian (corpus-based) for the simple reason that text messages are one of the most frequently used forms of communication within the constantly spreading communication technologies in Croatia (Žic Fuchs 2002-2003, Žic Fuchs, V. Broz 2004, Žic Fuchs, N. Tuđman Vuković 2008). The analysis aims to show how “new” rituals of communication reflect not only specific pragmatic parameters, but at the same time provide insights into the role and development of convention and shared knowledge, both seen as primarily cognitive categories. References: Grice, H. P. (1975). “Logic and Conversation.“. In Cole et al. Syntax and Semantics 3: Speech Acts, pp. 41-58. Elsevier. Lakoff, G. (1987) Women, Fire and Dangerous Things, What Categories Reveal about the Mind, Chicago: The University of Chicago Press Lakoff, G. & M. Johnson (1999) Philosophy in the Flesh, The Embodied Mind and Its Challenge to Western Thoughts, Basic Books. Langacker, R.W. (1987) Foundations of Cognitive Grammar: Theoretical Prerequisites, Stanford University Press Langacker, R.W. (1991) Foundations of Cognitive Grammar: Descriptive Application, Stanford University Press Sperber, D. and D. Wilson (1995) Relevance. Communication and Cognition. 2nd Edition. Oxford: Blackwell. Žic Fuchs, M. (2002-2003) “Communication Technologies and Their Influence on Language: An Example from Croatian.“ Studia Romanica et Anglica Zagrabiensia XLVII-XLVIII, pp. 597-608. Žic Fuchs, M and V. Broz. (2004) “Communication technologies and their influence on language: the Gricean maxims revisited.“ Informatologia 2, pp. 143-148. Žic Fuchs, M. and N. Tuđman Vuković. (2008) “Communication technologies and their influence on language: Reshuffling tenses in Croatian SMS text messaging.“ Jezikoslovlje, pp. 109-122.